Design of Computerized Patient Registration Application System at Tanjung Pati Health Center - Oktamianiza, Oktamianiza; Ilahi, Vitratul; Putri, Kalasta Ayunda; Yulia, Yulfa; Rahmadhani, Rahmadhani (UI Scholars Hub, 2024)
One of the shortcomings of manual patient registration systems is the procedures that affect the efficiency of service care to patients. Therefore, researchers are interested in designing a computerized patient registration application using Microsoft Access software. The type of research used is Research and Development (R&D). This research was conducted at Tanjung Pati Community Health Center, with in-depth interviews with two registration officers. The research results show that the data elements needed to design the patient registration application system, sourced from the Patient Registration Book, will be developed by creating an application system using UML modeling. The application system undergoes Black Box Testing with the result that all components run well. The application system is efficient, with an average comparison of manual patient registration time to system patient registration of 420:180 seconds for new patients and 360:33 seconds for existing patients. The application system is efficient according to the results of interviews with informants. Therefore, the design of the computerized patient registration application system using Microsoft Access meets the needs of the community health center and is efficient in terms of patient registration time. It is recommended that the patient registration application be used continuously in the medical records unit at Tanjung Pati Community Health Center.